LOOKING AT THE BASIS AND ORIENTATION OF ISLAMIC RELIGIOUS EDUCATION - Isna Aswaladani S.Pdi (Journal of Educational Science Learning and Research, 2024)
Islamic education is a part of the Islamic religion itself, therefore Islamic education should not run away from the meaning of Islam which aims to seek spiritual and material success in life. Therefore, the basis used in Islamic education is the arguments of the Qur'an and hadith which contain global or detailed information about Islamic education. In addition, other provisions are also used which in the history of Islamic education have been tested for their substance. Islamic education has two main orientations, namely first, serving Allah as the khaliq and understanding oneself as a khalifa on earth. This orientation is useful for designing students' beliefs so that they remain framed in Islamic values ​​and morality. Second, educating by understanding the nature of students, at this limit, not only Islamic education material is urgent but the method and learning process are also important